"Bury Don't Discuss": The Help-Seeking Behaviour of Family Members Affected by Substance-use Disorders. Issue 2 (3rd April 2019) - McDonagh, Debbie; Connolly, Nuala; Devaney, Carmel
ABSTRACT: The impact of substance-use disorders on families is well documented in the literature, with families experiencing physical, emotional and psychological stress. Also documented is the perceived stigma experienced by those living alongside family members with substance-use disorders. This paper focuses on the help-seeking behaviour of those affected by substance use within their families, exploring the ways in which informal, semi-formal and formal supports are drawn on. The prohibitive factors and barriers influencing decision making by families in need is also discussed. Through a qualitative research approach this study collates the perspectives of a cohort of family members in Ireland, with a view to informing and enhancing the design and delivery of support services. While participants positively endorsed most forms of formal support, services were sought and accessed in an ad-hoc fashion, with a range of psychological, geographical and emotional barriers presenting. The availability of services and the stigma associated with having family members affected by substance-use disorders are also highlighted. The paper provides opportunities and recommendations for potential ways of overcoming such barriers in order to access Family Support at an earlier stage.